Hybrid optical CDMA and DWDM system implemented under the influence of Non-linear effects - Naif Alsowaidi; Tawfig Eltaif; Mohd Ridzuan Mokhtar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A hybrid optical CDMA-DWDM system accommodating 12 optical CDMA users carried by 5 DWDM wavelengths at a data rate of 60Gb/s/wavelength with channel spacing of 0.4nm is implemented under the effect of four-wave mixing (FWM). It was found that the FWM effect could be minimized by the use of CDMA technology, where the energy of each bit is spread over the optical sequence code. Over a distance of 105.075km, significant performance of all optical CDMA users in terms of the BER is achieved. The results reveal that the inter-symbol interference (ISI) can be mitigated when the interval of optical signature sequence code is squeezed into 25% of the bit duration.